Hubungan Siklus dan Lama Menstruasi pada Mahasiswi Fakultas Kedokteran Ukrida dengan Nyeri Menstruasi - Raemon Alexandro Mau; Hendrik Kurniawan; Anna Maria Dewajanti (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2020)
Dysmenorrhea is a condition of intense pain during menstruation. Menstrual disorders can be in the form of prolonged menstrual duration, menstrual cycle interval disorders, bleeding disorders and other disorders related to menstruation. This study aimed to analyse the relationship between the cycle interval and duration of menstruation among students who experienced menstrual pain. This research was a descriptive study using a cross-sectional approach. This research was conducted at Krida Wacana Christian University (UKRIDA) from January to March 2020. A total of 72 students who were year I, II and III completed the questionnaires. The results showed that most of the respondents were 19 years of age (69,45%). The menarche age was at 12-13 years old (70,80%) with the mean age of 12 years old. Most of the respondents had normal menstrual cycles (79,2%) and menstrual duration (83,3%). Most of the respondents felt weakness or fatigue (83,33%). The Chi Square statistical test indicated the relationship between menstrual duration and the incidence of dysmenorrhoea (p < 0,05). However, there was no association between the menstrual cycle interval and the incidence of dysmenorrhoea (p value > 0,05).